Resposta terapêutica a inibidor de bomba de prótons em pacientes com disfonia e doença do refluxo faringolaríngeo - Pompeu, Clara Mota Randal (2020)
The laryngopharyngeal reflux disease (LPRD) is defined as aerodigestive signs and symptoms secondary to laryngeal and pharyngeal mucosa damage, due to gastrointestinal content reflux. LPRD is a new entity and was originally described as an extraesophageal manifestation of gastroesophageal reflux disease (GERD). LPRD is a rather prevalent condition, and dysphonia is an important symptom. This study aimed to evaluate the therapeutic response to a proton pump inhibitor (PPI) treatment, in dysphonic patients with LPRD, applying standardized scores. It was also evaluated if higher levels of the basal scores could predict a better response to the PPI treatment. A group of 21 patients with chronic dysphonia, over three weeks, were analyzed by Reflux disease questionnaire (RDQ), Reflux symptom index (RSI) and Reflux finding score (RFS). Patients were treated with pantoprazole 40mg, twice a day, for eight weeks, and it was considered as response a reduction of at least 50% of the scores, when compared to the basal results. After the course of treatment, there was a significant reduction of all the scores, however the clinical responses were higher than the laryngoscopic response. Higher scores in the RFS items erythema/hyperemia and diffuse laryngeal edema, before treatment, were present is the patients with better laryngoscopic response to the PPI. On the other hand, higher scores in the RFS item erythema/hyperemia, before treatment, were present in the patients with better complete response (clinical and laryngoscopic) to the PPI treatment. None of the scores before treatment was associated with better clinical response to the PPI. As conclusion, this study shows that there is a therapeutic response to PPI in dysphonic patients with LPRD, with the clinical response higher than the laryngoscopic one, after eight weeks. Higher scores of erythema/hyperemia before treatment were present in patients with a better complete response to the PPI. Further placebo-controlled studies, with a longer period of treatment, are necessary to confirm these results.